Characteristics of neonatal sepsis at a tertiary care centre in Western Uttar Pradesh, India: a hospital based retrospective study - Sachan, Divyata; Kharya, Pradip; Bajpai, Prashant K. (International Journal Of Community Medicine And Public Health, 2022)
Background: Due to the constantly changing genome of the organisms causing disease it is important to be updated regarding the pattern of distribution of microbes and their antibiotic susceptibility. The study was conducted with the aim to determine the risk factors, microbial profile, antimicrobial susceptibility and the outcome of neonates diagnosed with neonatal sepsis. Methods: A retrospective study was done using the data collected from medical records department of a tertiary care hospital. All the neonates diagnosed with clinical sepsis between 1to 31 January, 2019 were included in the present study. The data were analyzed using SPSS software version 24, IBM, corp., Chicago, U.S.A. Association between the outcome and independent variable were assessed using Chi square or Fischer exact test, while the level of association was assessed by univariate and multivariate analysis. Results: During the study period, 332 neonates were registered in the hospital out of which 89 were diagnosed with clinical sepsis. Most of the neonates (64.9%) presented with early onset sepsis and were term neonates (68.5%) with birth weight less than 2.5 kg (53.4%). Parameters like mode of delivery (OR:6.18; CI:1.30-29.32), birth weight (OR:9.14; CI:2.38-35.10) and gestational age (OR:7.33; CI:2.32-23.12) were statistically associated with neonatal outcome. All gram-positive organisms were sensitive to vancomycin and linezolid. Gram negative organisms were resistant to cephalosporins, amoxicillin- clavulanic acid and piperacillin-tazobactam. Conclusions: A high antibiotic resistance was observed among the isolated organism. The Gram positive and gram negative organisms were equally responsible for neonatal sepsis.